PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP TURN OVER INTENTION KARYAWAN PADA PT ROTI INDONESIA - Clarecia, Sheeren; wijaya, Shierli (Publika Citra Media, 2025)
This research analyzes the influence of leadership style, work environment, and work motivation on employee turnover intention at PT Roti Indonesia, a start-up company. In the era of globalization, effective leadership, a conducive work environment and high motivation are considered important to retain employees and improve company performance. Data was obtained through questionnaires distributed to employees, especially in the Live Stream Host, Content Creator and Management sections. The research results show that the right leadership style, positive work environment, and adequate work motivation have a significant effect on reducing turnover intention. This research has the implication that companies need to improve leadership strategies, create a supportive work environment, and provide motivation for employees to achieve company goals more effectively.